2022
DOI: 10.34306/ijcitsm.v2i2.84
|View full text |Cite
|
Sign up to set email alerts
|

Query Optimization In MySQL Database Using Index

Abstract: The quality of a database design has a significant impact on the quality of an information system. Even if a system has been running for a long time, a programmer may forget to optimize a query in MySQL, even though optimization is critical as the amount of data is enormous. MySQL has an index function for tables that helps to speed up database searches. In essence, the index will be beneficial if utilized by the user's interests and wants; otherwise, the index, constructed randomly and in large quantities, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Query Optimization In MySQL Database Using Index [10] The findings of this study revealed that the quality of the database design has a substantial influence on the quality of the information system. Even after a system has been in use for some time, a programmer could forget to optimize a MySQL query, even if optimization is crucial owing to the enormous amount of data.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Query Optimization In MySQL Database Using Index [10] The findings of this study revealed that the quality of the database design has a substantial influence on the quality of the information system. Even after a system has been in use for some time, a programmer could forget to optimize a MySQL query, even if optimization is crucial owing to the enormous amount of data.…”
Section: Literature Reviewmentioning
confidence: 92%
“…For example, the data query performance can be greatly improved through vertical segmentation and horizontal segmentation. Literature [5] states that using an index can help speed up database searches. In addition, it is necessary to reconsider the rules and conduct a thorough examination.…”
Section: Related Workmentioning
confidence: 99%
“…This scheme helps to transform data that is represented in high-level into structures of database management systems. Data query, data manipulation, data identity, and data access control are some of the key operations associated with MySQL [14]. This system's database is made up of various tables responsible for storing records that correspond to all authorised users accessing the system.…”
Section: Databasementioning
confidence: 99%